اللون ودلالته في شعر ابن الحداد الاندلسي: Color and Its Significance in The Poetry Of ibn Al-Haddad Al-Andalusi - Alsammarraie, Ban Kadhim Makki; Tawfiq Al-Aboud, Mohammed Hussein (SIBAWAYH Arabic Language and Education, 2024)
شغل موضوع اللون مختلف الدراسات العربية وغير العربية, العلمية والأَدبية, على حد سواء, وتتجلى فاعلية اللون في الشعر العربي على نحوٍ مميز, وذلك لارتباطها بالعواطف والمشاعر, وإنّ إِدراك الشعراء لمكانة اللون في نسيج النص الشعري يستدعي الوقوف على إمكانياتهم في توظيف هذا العنصر المهم, بوصفه مرتكزاً رئيسياً في المعجم الشعري الذي يميِّز شاعرا عن آخر, ومن بين البيئات العربية الزاخرة بالألوان (بلاد الاندلس) إذ شهدت اتساعاً في الناحية الحضارية والعمرانية, وازدهار الحياة, فضلاً عن طبيعتها الزاهرة بالألوان, فما كان من الشعراء إلا أنْ قيدوا تلك المشاهدات بشعرهم , بما تمتعوا بهِ من خيال خصب, فحملوا المعاني الرمزية التي تنهض بالألوان, من هذا كان اختيار موضوع البحث. تعتمد الدراسة على عدة مرتكزات أبرزها: خصوصية الشاعر، وخصوصية العرض الشعري، وخصوصية اللون، أما الدراسة فكانت من خلال تناول اللون ودلالته في شعر ابن الحداد حيث وقفتُ على طبيعة اللون في الأغراض الشعرية التقليدية من غزل ورثاء ووصف وفخر، وقد جاءت الدراسة في تمهيد عن سيرة الشاعر ابن الحداد الاندلسي، والمبحث الاول دلالة اللون في شعر ابن الحداد الاندلسي، والمبحث الثالث الدراسة الفنية في شعر ابن الحداد الاندلسي، اما خاتمة البحث فقد كانت عن اهم النتائج التي خرجت بها الدراسة. The topic of color has occupied diverse Arabic and non-Arabic studies, both scientific and literary alike. The effectiveness of color in Arabic poetry is particularly notable because it is linked to emotions and feelings. Poets’ awareness of the role of color within the fabric of poetic text necessitates examining their ability to employ this significant element, considering it a main pillar in the poetic lexicon that distinguishes one poet from another. Among the rich Arab environments with colors is Andalusia, which witnessed an expansion in civilization and architecture, and the flourishing of life, alongside its naturally vibrant colors. Poets captured these observations in their poetry, with the help of their fertile imagination, conveying symbolic meanings carried by colors, which motivated the choice of this research topic. The study relies on several main pillars, most notably: the individuality of the poet, the specificity of the poetic presentation, and the uniqueness of color. The study covers color and its significance in the poetry of Ibn Al-Haddad, focusing on the nature of color in traditional poetic themes like love, elegy, description, and pride. The research includes an introduction about the biography of Ibn Al-Haddad Al-Andalusi, the first chapter on the significance of color in his poetry, and the third chapter on the artistic study of his work. The conclusion of the research discusses the main findings of the study. Keywords: Color, Arabic poetry, emotions and feelings, Andalusia, Ibn Al-Haddad